2017
DOI: 10.18632/oncotarget.19437
|View full text |Cite
|
Sign up to set email alerts
|

The integrative clinical impact of tumor-infiltrating T lymphocytes and NK cells in relation to B lymphocyte and plasma cell density in esophageal and gastric adenocarcinoma

Abstract: BackgroundSeveral studies have demonstrated a prognostic impact of tumor-infiltrating T lymphocytes and natural killer (NK) cells in esophageal and gastric adenocarcinoma, but whether these associations differ by the density of tumor-infiltrating immune cells of the B cell lineage remains largely unknown.ResultsHigh infiltration of any T and NK lymphocytes investigated was in general associated with a favorable prognosis, but the strongest beneficial prognostic impact was seen in combination with high B lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 40 publications
(42 reference statements)
2
55
1
1
Order By: Relevance
“…39 Indeed, CD20 + B cells within the tumor microenvironment represent important and clinically relevant markers. 40,41 However, the role of CD20 + B cells in CRC remains unclear. 42 It was suggested that a lower density of CD20 + B cell infiltration correlated with poor clinical outcomes in the primary CRC 39 A high density of CD20 + B cells was therefore significantly correlated with an improved of the overall survival of patients.…”
Section: Discussionmentioning
confidence: 99%
“…39 Indeed, CD20 + B cells within the tumor microenvironment represent important and clinically relevant markers. 40,41 However, the role of CD20 + B cells in CRC remains unclear. 42 It was suggested that a lower density of CD20 + B cell infiltration correlated with poor clinical outcomes in the primary CRC 39 A high density of CD20 + B cells was therefore significantly correlated with an improved of the overall survival of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Expression levels of analyzed antigens in external cohorts of esophageal adenocarcinoma samples (TCGA n = 185) and normal esophageal mucosa samples (GTEx n = 300, ArrayExpress n = 6, TCGA n = 13 Patients with a combination of a high B and T cell infiltrate had the best prognosis, suggesting that tumor associated B and T cells synergistically inhibit tumor growth. 29 Distinct B cell subsets have been identified, which potentially promote or inhibit anti-tumor immune response. [32][33][34] The data described above highlight the prognostic relevance of B cells in solid cancer, but only very few studies analyzed the composition of B cell subsets in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Published data regarding the role of the immune system in the development of EACs have been conflicting [6][7][8][9]. Indeed, most studies on esophageal cancer analyze esophageal adenocarcinoma and esophageal squamous cell carcinoma together.…”
Section: Introductionmentioning
confidence: 99%
“…We focused on CD4 + T cells which orchestrate the immune system by producing a variety of different cytokines and are known to play a key role in several malignancies. Furthermore, a beneficial effect of inflammation in EACs is supported by recent studies showing that a high infiltration of CD3 + and CD8 + T cells correlates with a better prognosis [9,12,13]. However, a detailed characterization of pro-inflammatory CD4 + T cell subsets is missing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation